International Students’ Enhanced Academic Performance: Effects of Campus Resources - Banjong, Delphine N. (Journal of International Students, 2015)
This article investigates international students’ challenges, such as financial, English proficiency, loneliness/homesickness in the United States. In addition, it assesses how these students coped with such difficulties by making use of resources on campus, such as an international center, writing center, counseling center, and the student success center. Based on 344 responses, the results indicated that international students with language difficulties sought help from the writing and student success centers while those who reported financial stress and loneliness had visited the counseling center.